Comparison of anthropometric characteristics between world tour and professional continental cyclists - Miller, J.; Susa, K. (Journal of Science and Cycling, 2018)
This study analyzed the physical characteristics of the World Tour (WT) and Professional Continental (PC) cyclists during the 2018 racing season. Seven hundred sixty-three professional riders (27.9 +4.2 years, 1.81 +0.06 m, 68.6 +6.33 kg) were compared for physical characteristics (i.e. age, height, and body mass). All riders were classified within specialties based upon UCI points ((grand champion (GC), sprinter (S), time trialists (TT), one-day racer (OD)) earned during the previous season. As expected there were differences between the rider`s specialty as well as the different elite divisions of riders. Further results showed that there was no difference in Body Mass Index (BMI; kg.m2) in all riders, however, TT riders in the WT had a significant difference in body surface area (BSA) and frontal area (FA) when compared to the TT riders in the PC division. In conclusion, the present study identified specific physical characteristic differences between the different types of professional cyclist levels of riders (WT vs. PC) and within their specialty.